ANALISA KUALITAS PERMEN JELI KULIT PISANG MASAK SEHARI (MUSA PARADISIACA LINN) - Safitri, Ria Safitri; Yusuf, Liswarti; Faridah, Anni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
This aimstoanalyze theratio ofbanana peelextractandsugar40%: 60%, 50%: 50%, 60%: 40% on the quality ofthe color, texture, flavorandtaste ofjellycandy. Thisis thekind of researchexperimentusingacompletely randomized designwith 1factor which is theratio ofbanana peelextractandsugar(40%: 60%, 50%: 50%, 60%: 40%) with 3 time rapeat, that did in the Tata Boga Jurusan KKFTUNP workshopin July2013.The hypothesis show that there is an affect of the used ofbanana peelextractandsugar40%: 60%, 50%: 50%, 60%: 40%to the quality ofjellycandy. On the ratio of banana peel extractandsugar40%: 60% have a significant influenceon the quality ofthe colorbrown, lesschewytexture, is not flavor bananaandtasteverysweet. On the ratiobanana peel extractandsugarratio50%: 50% have a significant influenceonall indicators. And the ratiobanana peel extractandsugar60%, 40% had a significant influenceon the quality ofthe color, texture, andvery flavorfulbananatasteless sweet. Keywords: jellycandy, leather, pisang masak sehari.